2012
DOI: 10.1111/j.1524-475x.2012.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid derivatives and their healing effect on burns, epithelial surgical wounds, and chronic wounds: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Hyaluronic acid (HA) is a polysaccharide common to most species and is found in many sites in the human body, including the skin and soft tissue. A systematic review of the literature and meta-analysis was performed to identify randomized controlled trials, evaluating the use of HA derivatives in healing burns, epithelial surgical, and chronic wounds. Nine studies were identified, which met the search criteria and clinical endpoints of complete healing and percent wound size reduction when using HA vs. either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 44 publications
1
175
0
8
Order By: Relevance
“…82,83 By contrast, the mvShh provided a therapeutic effect after a single treatment over the 27-day duration of wound healing. Thus, the treatment effect observed in the mvShh group is due to the multivalent conjugation of Shh to HyA, and based on our in vitro results, we expect that the bioactivity advantage of mvShh complements any improvement in protein stability associated with conjugation to a long-chain biopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 By contrast, the mvShh provided a therapeutic effect after a single treatment over the 27-day duration of wound healing. Thus, the treatment effect observed in the mvShh group is due to the multivalent conjugation of Shh to HyA, and based on our in vitro results, we expect that the bioactivity advantage of mvShh complements any improvement in protein stability associated with conjugation to a long-chain biopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the product promotes healing when compared to other treatments (26) . In a randomized controlled trial, the efficacy of hyaluronic acid in the treatment of venous ulcers was compared to a neutral carrier.…”
Section: Discussionmentioning
confidence: 98%
“…93 Intraperitoneal injection of hyaluronan suppresses immune activation in a murine model of colitis 94 and may also promote the proliferation of antiinflammatory IL-10-secreting T-regulatory cells. 95 Numerous clinical studies have demonstrated the effectiveness of glycosaminoglycan preparations in enhancing wound healing, 96 and glycosaminoglycans may function similarly to enhance GI wound healing. 97 Characterization of human milk glycosaminoglycans and proteoglycans may guide the development of specific glycosaminoglycan-and proteoglycan-based immunomodulators.…”
Section: Anti-inflammatory Glycosaminoglycansmentioning
confidence: 99%